The glaciers climate change initiative: Methods for creating glacier area, elevation change and velocity products - Paul, Frank; Bolch, Tobias; Kääb, Andreas; Nagler, Thomas; Nuth, Christopher; Scharrer, Kilian; Shepherd, Andrew; Strozzi, Tazzio; Ticconi, Francesca; Bhambri, Rakesh; Berthier, Etienne; Bevan, Suzanne; et al. (Remote Sensing of Environment, 2015)
Glaciers and their changes through time are increasingly obtained from a wide range of satellite sensors. Due to the often remote location of glaciers in inaccessible and high-mountain terrain, satellite observations frequently provide the only available measurements. Furthermore, satellite data provide observations of glacier characteristics that are difficult to monitor using ground-based measurements, thus complementing the latter. In the Glaciers_cci project of the European Space Agency (ESA), three of these characteristics are investigated in detail: glacier area, elevation change and surface velocity. We use (a) data from optical sensors to derive glacier outlines, (b) digital elevation models from at least two points in time, (c) repeat altimetry for determining elevation changes, and (d) data from repeat optical and microwave sensors for calculating surface velocity. For the latter, the two sensor types provide complementary information in terms of spatio-temporal coverage. While (c) and (d) can be generated mostly automatically, (a) and (b) require the intervention of an analyst. Largely based on the results of various round robin experiments (multi-analyst benchmark studies) for each of the products, we suggest and describe the most suitable algorithms for product creation and provide recommendations concerning their practical implementation and the required post-processing. For some of the products (area, velocity) post-processing can influence product quality more than the main-processing algorithm. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Glacier area; Glacier elevation change; Glacier velocity; Optical and microwave remote sensing; Round robin experiment; Accuracy determination; Algorithm selection